Hepatitis B Virus Surface Antigen Subtype in Positive HBsAg Subjects in Mengwi District, Badung, Bali-Indonesia - Made Agus Hendrayana (Journal of Global Pharma Technology, 2019)
Indonesia is a country with a high prevalence of hepatitis B virus infection and can develop into chronic hepatitis in the community. Indonesia is a multiethnic country with a vast territory, so it is estimated that the prevalence of each hepatitis B virus subtype varies greatly in different regions. Sequences in the S region gene encoding amino acids can show hepatitis b virus subtypes through exclusive variations in subtype determinants of HBsAg. This hepatitis B virus subtype is epidemiologically important, because it can show differences in geography and ethnicity in its spread. This study aims to analyze the hepatitis B virus subtype in HBsAg positive subjects in Mengwi, Badung, and Bali-Indonesia. The subjects of the study were 75 patients who came to the Mengwi I Badung Primary Health Center. All serum samples were examined for HBsAg by the ELISA method. In HBsAg positive serum samples, hepatitis B virus subtypes are determined. The DNA is extracted from serum samples that are HBsAg positive. Amplification of portions of DNA S gene from serum HBsAg positive was performed by polymerase chain reaction first-round and second-round. The nucleotide sequence of the hepatitis B virus is converted into amino acid sequences and multiple alignments are performed. The hepatitis B virus subtype was determined by amino acid substitution analysis at positions 122, 127, 134, 159, 160 and 177 in the S gene assisted by using a computer program. The subjects with HBsAg positive were obtained from 11 out of 75 samples (14.7%). The results of hepatitis B virus subtype analysis found that almost all samples, 10 of 11 samples (90.9%) had adw2 subtypes, while one sample (9.1%) had adrq + subtype.Keywords: HBsAg, Subtype, HBV, Mengwi.